USE OF DIGITAL TWINS TO MITIGATE COMMUNICATION FAILURES IN MICROGRIDS - (:unkn) unknown (My University, 2023)
This work investigates digital twin (DT) applications for electric power system (EPS) resilience. A novel DT architecture is proposed consisting of a physical twin, a virtual twin, an intelligent agent, and data communications. Requirements for the virtual twin are identified. Guidelines are provided for generating, capturing, and storing data to train the intelligent agent. The relationship between the DT development process and an existing controller hardware-in-the-loop (CHIL) process is discussed. To demonstrate the proposed DT architecture and development process, a DT for a battery energy storage system (BESS) is created based on the simulation of an industrial nanogrid. The creation and validation of the BESS DT virtual twin and intelligent agent are emphasized, including a discussion of the design choices made during the process. The use of data communication for nanogrid coordination is introduced, including the possible detrimental effects of degraded or failed communication. The BESS DT is demonstrated during nominal and off-nominal events in the nanogrid, highlighting the DT’s ability to make decisions using only local measurements rather than relying on a data communication network for coordination. The results show that the BESS DT can increase nanogrid resilience by recommending actions in response to transient events in the nanogrid, even while the data communication network has degraded or failed.